A Case of Young Stroke due to Takayasu’s Arteritis (Journal of Armed Forces Medical College, Bangladesh, 2020)
The incidence of ischemic stroke among young adults is rising. Young individuals remain at high risk for recurrent stroke. As these patients generally still have a life expectancy of decades ahead, it is essential to find and educate them about the risk factors and causes of stroke to possibly prevent future vascular disease. One important but often missed cause of stroke in a young adult is Takayasu’s Arteritis. Takayasu’s Arteritis is a rare disease affecting the aorta and its main branches, causing arterial claudication and end-organ ischemia, including stroke. The etiology is unknown but is believed to be autoimmune. Early in the disease course, non-specific constitutional symptoms such as fever, malaise, and weight loss may occur this makes it a diagnostic challenge. Although, Takayasu’s Arteritis generally follows an insidious course, acute presentation with visual loss or stroke may also occur. It can be adequately treated if it is identified early. We describe a case of a 20-year-old officer cadet of Bangladesh Military Academy with no significant medical history who presented with acute ischemic stroke with right sided hemiplegia. He was evaluated as a young stroke case. Clinical examination revealed weak pulse in left upper limb and both carotids. Carotid bruits were also noted. CT angiogram findings revealed classical findings of Takayasu’s Arteritis. He responded well with steroid and immunosuppressive agent (Methotrexate). However, ultimately he could not be retained in service because of extremely strenuous nature of training, residual disability and chronic progressive and incurable nature of the disease.Journal of Armed Forces Medical College Bangladesh Vol.14 (2) 2018: 209-213